Assessment and Integrated Model of Language Components: Implications for Basic and Special Education Services in Mexico - Natalia Nieblas-Soto; Blanca Silvia Fraijo-Sing; Cesar Octavio Tapia-Fonllem; Melanie Moreno Barahona (LED Edizioni Universitarie, 2023)
VALUTAZIONE E MODELLO INTEGRATO DI COMPONENTI DEL LINGUAGGIO: IMPLICAZIONI PER I SERVIZI DI EDUCAZIONE BASICA E SPECIALE IN MESSICO Abstract Language development is important in a person's life because it is the basis for some learning processes; failure to achieve optimal levels of language development can result in problems related to reading. The present study had two main objectives: first, to assess the communication skills corresponding to the different language components, as well as their relationship with the literacy learning process in children; and second, to explain the relationship between oral communication skills, letter knowledge and reading ability. To achieve this goal, we examined reading ability, letter knowledge, and oral communication skills through three different instruments. We evaluated total of 121 children enrolled in three different elementary in Hermosillo, Mexico schools were evaluated. Among the findings, 54.5% of the participants scored less than one standard deviation below the mean in language development, indicating a possible delay in the reading skills. The results of our model also confirmed that reading ability is predicted by letter knowledge and oral communication skills. The model suggests that letter knowledge has an indirect effect on the relationship between oral communication skills and reading ability.